Relationship between Triple X Trisomy and ASD in A 2-Year-Old Child in Bom Despacho/Mg (London Journal of Medical and Health Research, 2025)
This study describes the case of a female child diagnosed with Triple X Syndrome and Autism Spectrum Disorder (ASD). The pregnancy was complicated, culminating in delivery at 36 weeks following medical recommendation due to vasa previa and umbilical cord insertion issues. Initial low food intake was observed, requiring intensive nutritional monitoring. During the first months of life, signs of developmental delay and atypical behaviors, such as lack of interaction and sensitivity to sensory stimuli, emerged, prompting the mother to seek specialized evaluation. The initial diagnosis suggested ASD; however, a second neuropediatrician requested genetic tests and additional clinical observations, leading to the discovery of X chromosome trisomy (47,XXX). This condition is associated with variable phenotypic characteristics and, in the described case, contributed to the autistic presentation. Multidisciplinary treatment, including equine therapy, speech therapy, swimming, and specific therapeutic interventions, resulted in significant improvements in the child's social interaction and development. The use of Risperidone helped control some behavioral symptoms. This case highlights the importance of genetic testing in underexplored diagnoses, as well as the essential role of early intervention in improving the quality of life for children with trisomies and ASD.
Keywords: macular hole; microinvasive vitrectomy; platelet-rich plasma; internal limiting membrane; Artery of Percheron; thalamic infarct; bilateral stroke; young adult; vertical gaze palsy; altered consciousness; cephalic screw; intrapelvic migration; hip fracture; Gamma 3 nail; PFNA nail; surgery complications.; ASD; Triple X Trisomy; Early Diagnosis